From needs analysis to task design: Insights from an English for specific purposes context. (January 2019) - Malicka, Aleksandra; Gilabert Guerrero, Roger; Norris, John M.
Needs analysis (NA) has long been argued to be the prerequisite for the design of language curricula or syllabi and the selection of tasks. According to Long (2005), a one-size-fits-all approach should be substituted by a careful examination of learners' needs in a particular domain or learner community. Despite the increasing practice of carrying out a NA as a first step in curriculum design, it is still unclear how exactly the insights obtained from NA can be used in meaningful ways to take informed decisions about task and syllabus design. This study attempts to fill this gap by applying the findings obtained in a NA in the domain of a hotel receptionist's job to the design of pedagogic tasks. The goals of this study were to obtain insights into what tasks are done in this domain (task selection), what kind of language use is associated with these tasks (task discourse analysis), how the information about perceived difficulty of tasks can be translated into instructionally manipulable variables (task difficulty), and in what order the resulting tasks should be presented to learners (task sequencing). The study design employed in-depth qualitative data collection, including 10 semi-structured interviews and three observations, and the sources were domain experts and domain novices. By linking the information obtained in the NA with a theoretical task complexity model, the study provides a detailed account of how real-life tasks can be translated into an articulated set of genuine and instructionally relevant pedagogic tasks.